“Strange beasts of the sea”: Captain Cook, the sea otter and the creation of a transoceanic American empire - Juliane Braun (Informa UK Limited, 2018)
On 12 July 1776, Captain James Cook and his crew left England in search of the famed Northwest Passage. Spanish, French, and Russian explorers before him had set out to find this Arctic waterway, which was thought to link the Atlantic and the Pacific Oceans and promised to open up a new, more direct trading route with Asia. After seven months of sailing up and down the North American Pacific Coast, however, Cook was forced to conclude that such a passage did not exist. His voyage nonetheless transformed the trade relations between Europe, the USA and Asia. By detailing the rich natural resources the crew encountered in the North Pacific, the published records of Cook’s last voyage alerted a vast reading public, both in Europe and the young USA, to the commercial opportunities emerging from the exploitation of these resources. Using the example of the sea otter, this article explores how new knowledge about the natural world in the Pacific and its dissemination through print culture not only sparked intense rivalries between European colonial powers, but also helped the newly independent USA establish itself as a transoceanic empire.